PELATIHAN PRECEPTORSHIP MODEL APPROACH PADA PERAWAT DAN BIDAN - Dani Prastiwi; Isrofah Isrofah; Sri Mumpuni Yuniarsih; Rahajeng Win Martani (LPPM Universitas Pekalongan, 2020)
Nursing higher education is a professional education that requires clinical learning as real experiences to learn about professionalism. Good clinical learning is supported by competent preceptor whom can be role as a role model. Therefore, clinical learning model training has needed to designs clinical guidance activities based on the cooperative and collaborative relationship development between the preceptor and students. The strategy used in this training is the pretest-posttest, lecture, discussion and roleplay methods.Keyword : Preceptorship, Nursing